0538 Effect of CPAP Adherence on Cognition in Older Adults with Mild Cognitive Impairment and Obstructive Sleep Apnea. (12th April 2019) - Richards, Kathy; Gooneratne, Nalaka; Dicicco, Barry; Hanlon, Alexandra; Moelter, Stephen; Onen, Fannie; Wang, Yanyan; Sawyer, Amy; Weaver, Terri E; Lozano, Alicia; Carter, Patricia; Johnson, Jerry C
Abstract: Introduction: Obstructive sleep apnea (OSA) is prevalent in older adults with mild cognitive impairment (MCI), and a growing number of studies suggest that OSA is associated with an increased risk for cognitive impairment. The purpose of this pilot clinical trial (Memories 1) was to determine if continuous positive airway pressure (CPAP) adherence predicts 1 year cognitive and everyday function in older adults with MCI and OSA. Methods: Older adults, aged 55-89 years, with apnea-hypopnea index >= 10 were referred from sleep and geriatric practices. CPAP adherence was defined as average CPAP use >= 4 hours per night over 1 year. Groups were 1) MCI, OSA, and CPAP adherent (MCI+CPAP), n=29, and 2) MCI, OSA, CPAP non-adherent (MCI-CPAP), n=25. Results: Psychomotor/cognitive processing speed (Digit Symbol) significantly improved in the MCI+CPAP group versus the MCI-CPAP group after adjusting for baseline age, race, and marital status (PE 1.68, SE 0.47, 95% CI = 0.73-2.62), with a 6-month effect size (ES) of 0.46, and a 1-year ES of 1.25. In addition, CPAP adherence had small to moderate effect sizes and a pattern of benefits across multiple domains of cognitive function, but these were not statistically significant, likely because of the small sample size and pilot nature of this study. Conclusion: To our knowledge, Memories 1 is the first prospective clinical trial to show that CPAP adherence in older adults with MCI and apnea significantly improves cognitive function. Memories 2, a larger, adequately powered study, is currently underway to confirm and extend our findings. Support (If Any): National Institute on Aging R01AG034682